PENGARUH SELF EFIKASI IBU MENYUSUI DALAM PEMBERIAN ASI EKSKLUSIF PADA IBU HAMIL TRIMESTER III - Erna Wati; Tri Sunarsih; Menik Sri Daryanti; Nurul Makiyah (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
The Effect of Self-Efficacy Breastfeeding Mothers in Exclusive Breastfeeding in Third Trimester Pregnant WomenBackground: : The self-efficacy of breastfeeding is a woman's belief in her ability to breastfeed a baby. Confidence owned by someone about something that has not been done that can increase motivation. Objective: To determine the effect of breastfeeding self-efficacy in exclusive breastfeeding for Trimester III pregnant women at the Puskesmas Teras Boyolali Regency. Methods: This research is a quasy experiment with a pre-test and post-test nonequivalent control group approach. Samples were all third trimester pregnant women with 36-40 weeks gestation in the Teras Health Center Work Area. The sampling technique used purposive sampling with inclusion and exclusion criteria as many as 34 respondents in the experimental group 34 in the control group. Data analysis using Wilcoxon signed rank test. Results : Statistical tests using Wilcoxon signed rank test were obtained (p = 0.000 <0.05) meaning that there was a significant effect on self-efficacy of breastfeeding in pregnant women. Conclusion: There is a significant influence on third trimester pregnant women in breastfeeding for breastfeeding self efficacy.